PRIORITAS PENGGUNAAN DANA DESA JEKAWAL KABUPATEN SRAGEN DI ERA PANDEMI COVID-19 - Arima Andhika Ayu; Royke Roberth Siahainenia; Elly Esra Kudubun (Jurnal Analisa Sosiologi, 2020)
Village is the smallest administrative area in Indonesia that has an autonomous government and is given the authority to manage all government affairs (Law No. 6 of 2014) regarding villages. Jekawal Village receives village funds to prioritize, its use in increasing empowerment and dealing with unexpected disasters, such as Covid-19 pandemic. The purpose is determine the priority of village fund-spend in improving community and emergency respon’s village to Covid-19 pandemic era in 2020 fiscal year. This study used a qualitative-descriptive method. Techniques of data collections are from observation, interviews, and literature study. This research is analising to data reductions, data presentations, and found the conclusions. The research’s use structural-functional theory "AGIL" from Tallcot Parsons. And the results are shows that each village received village funds, that is Jekawal village that the village funds were prioritized for community empowerment and emergency response to village in the Covid-19 pandemic era.Keywords: Priority Of Village Funds Spend, Community Development, Covid-19 Emergency Response. AbstrakDesa merupakan wilayah administrasi terkecil di Indonesia yang memiliki pemerintahan otonom dan diberikan kewenangan untuk mengurusi mengatur semua urusan pemerintahan (Undang-Undang No. 6 tahun 2014) tentang desa. Desa Jekawal mendapatkan bantuan dana desa untuk memprioritaskan penggunaan dalam meningkatkan pemberdayaan dan menangani bencana yang tak terduga, seperti saat ini di era pandemi covid-19. Tujuan penelitian ini untuk mengetahui prioritas penggunaan dana desa dalam pemberdayaan masyarakat dan tanggap darurat desa di era pandemi covid-19 tahun anggaran 2020. Penelitian ini menggunakan metode kualitatif-deskriptif, teknik pengumpulan data melalui observasi, wawancara, dan studi kepustakaan. Analisis data yang digunakan yaitu reduksi data, penyajian data, dan menarik kesimpulan. Hasil penelitian membuktikan setiap desa mendapatkan dana desa salah satunya Desa Jekawal dimana dana desa dalam prioritas penggunaan untuk pemberdayaan masyarakat dan tanggap darurat dana desa di era pandemi covid-19 dengan penggunaan teori struktural fungsional “AGIL” dari Tallcot Parsons.Kata Kunci : Prioritas Penggunaan Dana Desa; Pemberdayaan Masyarakat; Tanggap Darurat Covid-19.